Sensorial and physicochemical profile of chihuahua cheese considering consumer preferences - Martínez-Ruiz, Nina del Rocío (2018)
The milk industry and its derivatives are an important Mexican productive sector. This agroindustry sector in Chihuahua, Mexico, is one of the most important in the economy of the region. Chihuahua cheese is a dairy product that distinguishes the state. Because of its characteristics, it is the second most commercialized and consumed in the country, after the “panela” cheese. The objective of this study was to assess the sensory, physicochemical characteristics of Chihuahua cheese and its relationship with consumer preferences. Ten trained judges evaluated the odor, taste and mouthfeel attributes on 10 cheese samples produced in Chihuahua. The proximate composition, pH, acidity, sodium content and protein profile were determined. We assessed the preference via preference-ranking and acceptance tests with 120 consumers. The Chihuahua cheese was characterized by its medium to medium-high odor of fresh milk, cooked milk, and melted butter; with mediumlow intensity taste, firmness, moistness and fat character. The composition and other characteristics varied between samples. The protein profile showed peptides from 24.0 to 34.7 kDa. The physicochemical properties of the cheese determine its sensory profile, the consumer preferences, and the acceptance or rejection of the product. From the consumer preferences in this study, we elaborated a physicochemical and sensory profile model of Chihuahua cheese, which can support the standardization of Chihuahua cheese manufacturing, quality and acceptance.